The Effect Of Investment Literacy And Perspectives On Investment On The Ability To Manage Investments - Linzzy Pratami Putri; Irma Christiana; Delyana Rahmawany Pulungan; Isna Ardila (AIBPM Publisher, 2019)
The purpose of this study is to examine and analyze the effect of investment literacy and perspectives on investment on the ability to manage investments, both partially and simultaneously. Suggestions used in this study are associative. The population in this study were all students of the Faculty of Economics and Business, Muhammadiyah University, North Sumatra. Data collection techniques in this study using documentation techniques. Data analysis techniques in this study used the Classic Assumption Test, Multiple Regression, Hypothesis Test (t Test and F Test), and the Coefficient of Determination. Data processing in this study uses SPSS software version 23.00. The results of the study prove the fact that partially and simultaneously have a positive and significant effect on investment literacy and perspective on investment on the ability to manage investment.